Whole-blood culture-derived cytokine combinations for the diagnosis of tuberculosis - Østergaard, Anne Ahrens; Feddersen, Søren; Barnkob, Mike B.; Lynggaard, Rasmus Bank; Karstoft, Amanda Cecilie Annie; Borup, Maria; Titlestad, Ingrid Louise; Jensen, Torben Tranborg; Hilberg, Ole; Wejse, Christian; Bjerrum, Stephanie; Blaabjerg, Morten; et al. (Frontiers in Immunology, 2024)
The diagnosis of tuberculosis (TB) disease and TB infection (TBI) remains a challenge, and there is a need for non-invasive and blood-based methods to differentiate TB from conditions mimicking TB (CMTB), TBI, and healthy controls (HC). We aimed to determine whether combination of cytokines and established biomarkers can discriminate between 1) TB and CMTB 2) TB and TBI 3) TBI and HC. We used hemoglobin, total white blood cell count, neutrophils, monocytes, C-reactive protein, and ten Meso Scale Discovery analyzed cytokines (interleukin (IL)-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12p70, IL-13, interferon (IFN)-ɣ, and tumor necrosis factor (TNF)-α) in TruCulture whole blood tubes stimulated by lipopolysaccharides (LPS), zymosan (ZYM), anti-CD3/28 (CD3), and unstimulated (Null) to develop three index tests able to differentiate TB from CMTB and TBI, and TBI from HC. In 52 persons with CMTB (n=9), TB (n=23), TBI (n=10), and HC (n=10), a combination of cytokines (LPS-IFN-ɣ, ZYM-IFN-ɣ, ZYM-TNF-α, ZYM-IL-1β, LPS-IL-4, and ZYM-IL-6) and neutrophil count could differentiate TB from CMTB with a sensitivity of 52.2% (95%CI: 30.9 – 73.4) and a specificity of 100 % (66.4-100). Null- IFN-ɣ, Null-IL-8, CD3-IL-6, CD3-IL-8, CD3-IL-13, and ZYM IL-1b discriminated TB from TBI with a sensitivity of 73.9% (56.5 - 91.3) and a specificity of 100% (69.2-100). Cytokines and established biomarkers failed to differentiate TBI from HC with ≥ 98% specificity. In summary, selected cytokines may serve as blood-based add-on tests to detect TB in a low-endemic setting, although these results need to be validated.